Zoonosis and veterinary waste disposal in rural practice = Zoonosis y disposición de desperdicios veterinarios en la práctica rural - Huertas, Pablo Sebastian (2018)
The objectives of this study were to estimate: (a) the frequency of zoonoses in largeanimal veterinarians from rural areas of the province of Buenos Aires, Argentina, and (b) todescribe the use and disposal of personal protective equipment (PPE) and selective veterinaryclinical waste. A cross-sectional study was carried out on large animal veterinary practitionersin the Province of Buenos Aires (n = 106). One third (29.2%) of them had been diagnosed with azoonosis by laboratory-methods, being brucellosis the most frequent (22.6%). The more yearspassed since their graduation, the greater the chances of becoming ill (p < 0.001). Gloves werethe most adopted PPE; however, other elements had little or no use at all. Older and experiencedprofessionals used PPE less frequently than young inexperienced practitioners. Some PPE wasfrequently reused and the final disposal of veterinary waste was often inappropriate. A changein behavior is an urgent need to preserve not only the veterinarians’ health but also theirfamilies’ wellbeing and to ensure proper disposal of potentially hazardous waste.